Shadows of the White City - Green, Jocelyn (Green, Jocelyn. Windy City saga, 2021)
"When Sylvie Townsend's Polish ward, Rose, goes missing at the World's Fair, her life unravels. Brushed off by the authorities, Sylvie turns to her boarder and Rose's violin instructor, Kristof Bartok, for help searching the immigrant communities. When the unexpected happens, will Sylvie be able to accept the change that comes her way?"--